Konsep Ammah Menurut Nawawi Al-Bantani Serta Relevansinya Dengan Kesetaraan Gender - Masfufah, Latifatul; Maimun, Maimun; Zikri, Zikri (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
In this study, the philosophical basis of Nawawi al-Bantani's book Uqūd al-Lujayn will be analyzed. This book places the husband-wife relationship within a patriarchal framework and typically refers to the wife as a "slave" or "captive," a description that has sparked contemporary controversy. The purpose of this study is to examine the concept of Ammah according to Nawawi al-Bantani and its relevance to gender equality. Using documentation based on secondary data and literature, including books, articles, and journals related to Nawawi al-Bantani's thoughts on the concept of Ammah, as well as relevant perspectives and other sources reviewed thru content analysis, this study combines qualitative descriptive methods with a library research approach. The research findings indicate that the concept of Ammah is interpreted as protection and compassion toward wives, demonstrating its continued relevance in contemporary Islamic family law. However, the concept of Ammah in terms of restrictions on women and the symbolization of subordination is considered contradictory to the principle of gender equality. This research affirms the importance of recontextualizing classical Islamic legal thot to align with the demands of justice and harmony in contemporary family relationships